Система базовых несущих конструкций радиоэлектронных средств: состояние проблемы - Romanova, Yu. S.; Sherin, K. Yu. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
The dynamics of solving the problem of creating a unified system of basic supporting structures of radio electronic equipment (BSS REE) are shown. The nomenclature, structure, and parameters of the structural elements and modules of the BSS REE system are considered for the development of advanced automated control systems for various industrial applications.